PENGARUH MODEL INQUIRY LEARNING DENGAN BANTUAN MEDIA MAKE A MATCH TERHADAP HASIL BELAJAR CIRI-CIRI MAKHLUK HIDUP SISWA KELAS 3 SEKOLAH DASAR - Luthfi Rahmania; Septiyana Astri Wulandari; Wahyu Kurniawati; Anisya Al Husna (JURNAL LENTERA [PENDIDIKAN PUSAT PENELITIAN LPPM UM METRO], 2024)
This study intends to evaluate the influence of the inquiry learning learning model with the help of make a match media on the learning outcomes of grade 3 students in Gulurejo Village in understanding the characteristics of living things. A descriptive qualitative approach is used in this study, through data collection methods, namely observation, documentation, and interviews. The research subjects consisted of grade 3 students in five elementary schools in Gulurejo Village. The results of the study show that the implementation of the inquiry learning model with the help of make a match media has a positive influence on student learning outcomes. Students who participated in this activity showed a significant improvement in their understanding of the characteristics of living things such as moving, breathing, excreting waste, and reproducing. In addition, this model also assists students in the development of critical thinking, analysis, and scientific inquiry skills. Based on data analysis using the paired sample t-test, a significant difference between the pre-test and post-test scores of students was found, namely the significance value of 0.002 (p < 0.05). In this case, it shows that the inquiry learning model with the help of make a match media is effective in improving student learning outcomes. This study has concluded that the use of interactive and innovative learning models can create a more fun and meaningful learning environment for students, as well as encourage active involvement and collaboration between students in the learning process.